The impact of the 2010 flood on the morphology in the southern part of the Jeziorsko Reservoir bottom - Rdzany, Zbigniew; Szmidt, Aleksander; Frydrych, Małgorzata; Kossowski, Maciej (Acta Geographica Lodziensia, 2022)
Issues related to the transport of fluvial debris and deposition of alluvia in reservoirs have been the subject of intense research in many centres around the world for about a century. Studies of the silting rate of dammed reservoirs and the sedimentological characteristics of the deposited material are important from the point of view of the service life of these reservoirs. A reduction in capacity of 80% or even, according to many scholars, of 50% reduces the capacity of reservoirs to fulfil various important functions for which they are designed. In the case of the Jeziorsko Reservoir (central Poland), the problem of sediment accumulation was investigated by Wicher- -Dysarz and Dysarz (2016) after 30 years of its existence. The scholars applied several research procedures, adopting geodesic profiling as the main method. The data they obtained varied depending on the applied method, which indicates significant differences in their precision. For this reason, new methods must be sought. This article attempts to determine geomorphological and sedimentological changes in the southern part of the Jeziorsko Reservoir that occurred in the years 2009–20011 mainly as a result of the flood in the Warta River valley in May and June 2010. The flood was one of the largest in this valley in the last century. The main source of data was LiDAR measurements carried out in the years 2009 and 2011, i.e. one year before and one year after the catastrophic flood. Certain spatial data were visualised, including the extent of depositional processes, volume and distribution of sediment thickness, altered shapes of relief forms in the upper part of the reservoir, as well as other related environmental changes. Aerial and satellite photography taken throughout the reservoir’s existence and archival cartographic, geological, hydrological and botanical data were used for this purpose. It was found that the results of the flood included partial filling of channels within the delta, the disregulation of the outline of previously originated relief forms, and the formation of hundreds of fine hills of between several and twenty metres in diameter and rarely exceeding 1 metre in height. The thickness of the sediments deposited as a result of the flood in the vast majority of the area is 0.5–0.7 m, with the occurrence of small areas of slight depressions. The extent of flood-related debris accumulation was found to be linked with the most elevated, middle and northern part of the delta, particularly in the zone of tall vegetation. The authors also conducted a discussion of the previous research results from other authors, mainly in the context of silting of the reservoir. The effectiveness of sediment deposition as a result of the flood was primarily influenced by the following: existing depressions in the form of channels, existing narrowings or broadenings of the flood water flow zone (constrained flow, free flow), and concentrations of vegetation – especially tall (riparian and scrub) vegetation. It was found that, although lidar data are more precise than those obtained using other methods, one must take into account the possibility of errors that are difficult to estimate. This applies mainly to water-covered areas and, to a lesser extent, to accumulations of small convex forms. Due to this, part of he area was excluded from further analyses. Measurement using the trapezoidal rule in Golden Software Surfer 16 revealed 667 986 m3 of deposited material. This means that the overall cubic capacity of debris deposited during the 2010 flood may exceed the entire accumulation to date. For this reason, siltation analyses should account for the possible occurrence of catastrophic events, especially floods.